2017
DOI: 10.3748/wjg.v23.i9.1697
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes mellitus, insulin resistance and hepatitis C virus infection: A contemporary review

Abstract: AIMTo summarise the literature data on hepatitis C virus (HCV)-infected patients concerning the prevalence of glucose abnormalities and associated risk.METHODSWe conducted a PubMed search and selected all studies found with the key words "HCV" or "hepatitis C virus" and "diabetes" or "insulin resistance". We included only comparative studies written in English or in French, published from January 2000 to April 2015. We collected the literature data on HCV-infected patients concerning the prevalence of glucose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
90
1
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(107 citation statements)
references
References 124 publications
4
90
1
6
Order By: Relevance
“…We identified a significant inverse correlation between the duration of HCV infection and the quantitative decrease in liver stiffness, r s =-0.326, p=0.017, N=53, but this association was not statistically significant when comparing the qualitative regression in liver fibrosis, despite the fact that patients who achieved a one stage decrease in fibrosis had a slightly lower median (IQR) duration of HCV infection, 12 (7)(8)(9)(10)(11)(12)(13)(14)(15)(16) years, compared with those who did not achieve regression of liver fibrosis, 13.5 (9-16) years (U=320.5, p=0.578, r=0.08).…”
Section: Duration Of Hcv Infectionmentioning
confidence: 87%
See 1 more Smart Citation
“…We identified a significant inverse correlation between the duration of HCV infection and the quantitative decrease in liver stiffness, r s =-0.326, p=0.017, N=53, but this association was not statistically significant when comparing the qualitative regression in liver fibrosis, despite the fact that patients who achieved a one stage decrease in fibrosis had a slightly lower median (IQR) duration of HCV infection, 12 (7)(8)(9)(10)(11)(12)(13)(14)(15)(16) years, compared with those who did not achieve regression of liver fibrosis, 13.5 (9-16) years (U=320.5, p=0.578, r=0.08).…”
Section: Duration Of Hcv Infectionmentioning
confidence: 87%
“…We also assessed whether there is an association between the regression of liver fibrosis with classical prognostic factors previously used for calculating the chance of obtaining SVR following interferon-based treatment, such as: younger age (7,8), female gender (9), IL28B CC rs12979860 (10) or other genetic polymorphisms (11,12), baseline viral load below 600,000 IU/mL (13,14), absence of diabetes mellitus (15), shorter duration of HCV infection (16) calculated as the time (years) since the first positive anti-HCV test, and absence of surrogate markers for advanced liver disease at baseline.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to hepatic steatosis, several studies have reported the correlation of hepatitis C virus and diabetes mellitus . As we all know, obesity and lipid metabolism disorders often affect glucose homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…Among these extrahepatic complications, a growing body of evidence has particularly shown that HCV infection is strongly associated with the dysregulation of glucose homoeostasis such as insulin resistance (IR) and type 2 diabetes (T2D). Studies thus far and especially a recent retrospective study with 2435 patients have confirmed the relationship between HCV infection and T2D: People infected with HCV are 4 times more likely to develop T2D; clearance of HCV with direct‐acting antivirals significantly decreases HbA1c and the dependence on anti‐diabetes medications; and HCV‐infected patients with uncontrolled glucose are at higher risk to develop advanced liver fibrosis, HCC, and exhibit decreased sustained virologic response (SVR) to traditional interferon treatment.…”
Section: Introductionmentioning
confidence: 96%